The neuromuscular transmission of the SOD1 (G93A) mouse model of amyotrophic lateral sclerosis - Rocha, Mariana Frota Cúcio de Moraes, 1986- (2013)
Tese de mestrado, Neurociências, Faculdade de Medicina, Universidade de Lisboa, 2013